Synthesis, characterisation, crystal structure and antimicrobial evaluation of novel 6-alkoxyergosta-4,6,8(14),22-tetraen-3-one derived from natural ergosta-5,7,22-trien-3β-ol - Bacho, Mitchell; Artigas, Vania; Araya-Contreras, Tiare; Bittner, Mauricio; Escobar, Carlos A.; Fuentealba, Mauricio; Becerra, Jose; Fajardo Morales, Victor Manuel; San Martin Barrientos, Aurelio Del Carmen (My University, 2023)
In this study, we report a facile transformation starting from 5 alpha-hydroxyergosta-7,22-dien-3,6-dione (1) to afford two novel compounds: 6-methoxyergosta-4,6,8(14),22-tetraen-3-one (2) and 6-ethoxyergosta-4,6,8(14),22-tetraen-3-one (3) using alcoholic acid catalysis. Their structures were elucidated using NMR experiments, FT-IR, MS and X-ray analysis. These compounds were evaluated for antibacterial activity using the disk and broth diffusion test. In those tests, compound 3 was found to be the most significant antibacterial agent. In general, compounds 1-3 showed inhibition zone in the range of 7.00-12.3 mm for S. aureus and S. mutans, meanwhile for Gram-negative bacteria E. coli and Pseudomonas sp. was found to be in the range of 7.00-8.00 mm. For the most active, compound 3, MIC was significantly lower than that reported for ergosterol, in a value of 160 mu g/mL. Overall, these compounds were more active than their natural precursor.
Keywords: x-ray analysis; sterol derivatisation; antimicrobial activity; alcoholic acid catalysis